Associations between epidermal growth factor receptor and topoisomerase II-alpha gene copy number variations, human papillomavirus positivity, and cytologic analysis in cervical cell lesions - Kaya, Işın; Sivrikoz, OyaNermin; Etlik, Özdal; Gök, Abdülkadir (Indian journal of pathology & microbiology, 2017)
Cervical cancer is the second most common gynecologic cancer worldwide. Human papillomavirus (HPV) infection is a leading etiological factor in cervical carcinoma.The aim of this study was to compare HPV positivity, EGFR and TOP2A gene copy number variations and cervical cytologic findings. The study group comprised 100 female volunteers between 21-64 years old. Cytologic analysis was performed using the liquid-based cytology technique. HPV DNA testing was performed in all cases. Copy number variations that belong to EGFR and TOP2A genes evaluated by using FISH analysis. Cytologic analysis of the cervical samples revealed abnormal findings in 13 of the 100 study subjects. ASCUS , LSIL, HSIL were determined in 8, 2 and 3 cases respectively as the result of cytologic analysis on all cases. Forty-one (41%) of the 100 women were HPV-positive. Chi-square analysis confirmed that HPV-positive women showed significantly more abnormal cytology (P = 0.035). EGFR deletion, TOP2A deletion and both EGFR and TOP2A deletion were determined in 1, 8 and 1 cases respectively. We found no statistical difference in abnormal cytologic findings between subjects with these gene deletions and subjects with normal gene copy numbers (P > 0.05 for both). No cases of amplification were determined for either gene. As a result, HPV positivity and the determination of changes that may occur in the gene copy number in patients with abnormal cytology can be an important tool on account of prognosis. Research with more patients may be suggested.